Clinical and gross pathological findings of Johnes disease in a calf: A case report - Jesse, Faez Firdaus Abdullah; Bitrus, Asinamai Athliamai; Abba, Yusuf; Sadiq, Muhammad Abubakar; Chung, Eric Lim Teik; Hambali, Idris Umar; Lila, Mohd Azmi Mohd; Haron, Abd Wahid (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This case report describes a clinical case of Johnes disease (JD) in a Friesian calf aging one and half years. Materials and methods: Physical examination of the calf was carried out, history of the farm as well as samples for laboratory examinations were obtained. The laboratory examinations included hematological examinations by direct wet mount, hematocrit centrifugation technique and Giemsa stain, biochemical evaluation of serum, bacterial culture and isolation from feces and aspirate from the swollen jaw. Results: Clinical history showed that the farm had a history of JD, and routine health screening revealed that one of the calves had clinical signs suggestive of Johnes disease. Physical examination of the calf revealed a lumpy jaw, enlarged bilateral pre-scapular and pre-femoral lymph nodes, while hematological and biochemical findings showed a normocytic normochromic anemia, severe leukocytosis with neutropilic left shift and lymphocytosis with hyperproteinemia characterized by hyperglobulinemia. Fecal bacterial tests showed the presence of acid fast bacilli. Based on the history and laboratory findings, the cow was diagnosed with JD. In order to ensure effective control measures, the calf was culled from the heard. Postmortem examination revealed inflamed pre-scapular and pre-femoral lymph nodes with the presence of paramphistomes in the rumen mucosa. Conclusion: Since JD is a chronic disease that lingers in livestock farms, there is need for early identification and culling of infected animal in order to limit its devastation on the farm. http://doi.org/10.5455/javar.2016.c165